«Թաքուն, քողարկված» հասկացության բայանվանական և գոյականական դրսևորումները վաղնջահայերենից եկող մի արմատի հայ-իրանական ստուգաբանական քննության լույսի ներքո - Դալալյան, Տորք (ՀՀ ԳԱԱ ԼԻ հրատարակչություն)
In this paper, we make an attempt to etymologize through a comprehensive historical and comparative analysis Arm. կուզ [kouz], which meant ‘cat’ in Classical Armenian (Grabar). This word, traditionally considered to be of Iranian origin, has not been subjected to a deeper research. As a result, cognates and possible related variants have remained in the shadows. In one of the archaic languages of the region, Ossetic, a descendant of Alanian, the verbal root qwǝz- / ğuz- means ‘to sneak up’, ‘to sneak in secretly’. This lexical coincidence in Armenian and Ossetic can be considered as an ancient Armenian-Alanian isogloss, bearing in mind also the fact that many lexical and semantic varieties of this root have been preserved in the Armenian dialects. Целью статьи является попытка этимологизировать посредством всестороннего историко- сравнительного анализа арм. կուզ [kouz], означающее "кот" в классическом армянском языке (грабар). Это слово, традиционно считающееся иранского происхождения, не подвергалось более глубокому исследованию, в результате чего когнаты и возможные родственные варианты остались в тени. В одном из архаичных языков региона, осетинском, потомке аланского, глагольный корень qwǝz- / ğuz- означает "красться", "подкрадываться", "пробираться тайком". Это лексическое совпадение в армянском и осетинском можно считать древней армяно-аланской изоглоссой, имея ввиду также то обстоятельство, что в армянских диалектах сохранилось множество лексических и семантических разновидностей данного корня.
Keywords: Լեզվաբանություն; Ստուգաբանություն